2013
DOI: 10.1093/rheumatology/ket330
|View full text |Cite
|
Sign up to set email alerts
|

Onset age affects mortality and renal outcome of female systemic lupus erythematosus patients: a nationwide population-based study in Taiwan

Abstract: Female patients with late-onset SLE carried a higher risk of mortality than those with adult-onset disease in the presence of co-morbidities. Juvenile-onset SLE patients were at greatest risk of mortality, which is probably due to disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 27 publications
4
44
1
2
Order By: Relevance
“…In another study in an attempt to minimize the effect of age on mortality, an age-matched control group was included, and, in conclusion, death risk in late-onset SLE patients was detected to be higher than that in adult-onset SLE patients. 13 The study of Merola et al, 5 likewise, pointed out advanced age at the diagnosis as a predictor of decreasing 10-year survival, in particular. 5 In the study of Bernatsky et al, 1 short disease term (<1 year) has increased standardized mortality ratio 5.4 times (95% confidence interval 4.7-6.3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study in an attempt to minimize the effect of age on mortality, an age-matched control group was included, and, in conclusion, death risk in late-onset SLE patients was detected to be higher than that in adult-onset SLE patients. 13 The study of Merola et al, 5 likewise, pointed out advanced age at the diagnosis as a predictor of decreasing 10-year survival, in particular. 5 In the study of Bernatsky et al, 1 short disease term (<1 year) has increased standardized mortality ratio 5.4 times (95% confidence interval 4.7-6.3).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 There are studies which have associated survival with the age at the diagnosis of SLE. 3,5,[11][12][13] Being diagnosed after the age of 50 years has been associated with poor survival. 3 Ruiz-Irastorza et al 11 have identified older age at the time of diagnosis as an independent risk factor for mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of SLE among the Asian SLE population beyond the age of 50 years is reported to be 4-10%. [40][41][42] Though SLE is more common in females, the female preponderance reduces in late-onset disease. [42][43][44][45] This drastic change is due to the absence of female sex hormones in elderly patients.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…63 In fact, mortality rates have been found to be higher in these patients due to infections, with 5, 10 and 15-year survival rates being 80.4%, 56.5% and 31.7% respectively. 40,41,43 Gout Gout is a heterogeneous disorder that results in the deposition of uric acid salts and crystals in and around joints and soft tissues. Elderly-onset gout (EOG) is appearance of gout after the age of 60 or 65 years and present with atypical findings.…”
Section: Outcomementioning
confidence: 99%
“…Juvenile SLE (JSLE) is characterized by an exaggerated immune response with highly activated autoreactive B lymphocytes, dysregulated immune regulatory pathways, and frequent involvement of the renal, hematological and central nervous systems (3)(4)(5). Children with JSLE also have a higher disease severity and a significantly higher mortality risk compared to patients with adult onset disease (6,7). Timely diagnosis and treatment have been shown to significantly improve the prognosis and the clinical management of JSLE (8).…”
mentioning
confidence: 99%